From 'Lugal. Gal' to 'Wanax' : kingship and political organisation in the Late Bronze Age Aegean - Kelder, Jorrit M.; Waal, Willemijn (Sidestone Press, 2019)
In this book the much-debated problem of political organization in Mycenaean Greece (ca. 1400-1200 BC) is analysed and contextualised through the prism of archaeology and contemporary textual (Linear B, Egyptian and Hittite) evidence. From the early 14th century BC onwards, Hittite texts refer to a land Ahhiya(wa). The exact geographic position of this land has been the focus of academic debate for more than a century, but most specialists nowadays agree that it must have been a Hittite designation for a part, or all of, the Mycenaean world. On at least two occasions, the ruler of Ahhiyawa is.